Pengaruh Perilaku Kepemimpinan Terhadap Kinerja Madrasah di MIN Kota Bandar Lampung - Mahmud Sahroni; Muhamad Yasin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The study aimed to reveal the influence of the behaviour of madrasah principals on the performance of State Elementary Schools in Bandar Lampung City. The research method used was a regression study with a population of 493 and a sample of 123 people spread across 12 MIN using cluster random sampling techniques. The research instruments used were rating scales and Likert scale questionnaires that had been tested for validity and reliability. The research data were analyzed using simple regression techniques. The results of the data analysis showed that: the behaviour of madrasah principals has a direct relationship. The behaviour of madrasah principals in Bandar Lampung City has an effect on school performance, but it is not significant.